The influence of sales and leverage on tax avoidance: evidence from Indonesian public companies - Sulistiana, Indra; Febriana, Febby; Agung Wibowo, Cokorda (Trigin Publisher, 2025)
Tax avoidance remains a critical issue in corporate financial management, with earlier research showing mixed results regarding the impact of leverage and sales growth. The goal of this study is to investigate the impacts of leverage (measured by DER) and sales growth on tax avoidance, based on the trade-off theory of tax avoidance (DeAngelo & Masulis, 1980) and prior evidence that sales volatility affects tax planning flexibility (Chen et al., 2023), measured by the Effective Tax Rate (ETR), in Indonesian public companies. Using secondary data from 22 consumer goods businesses listed on the Indonesia Stock Exchange (IDX) between 2020 and 2023, multiple linear regression analysis was employed. Traditional assumption tests confirmed model validity. The results indicate that simultaneously, leverage and sales growth significantly impact tax avoidance (F-statistic=3.906, p=0.031). Partially, sales growth does not significantly impact tax avoidance (t-statistic=-0.776, p=0.444), while leverage has a substantial impact (t-statistic=2.436, p=0.021). The determination coefficient (R²) was 0.212, indicating that 21.2% of the variation in tax avoidance is accounted for by the model. Leverage is a significant factor influencing tax avoidance, implying that firms with higher debt levels engage in strategic tax planning. However, generalizability is limited by the relatively small sample size (N=22) and exclusive focus on consumer goods sector. These findings suggest that Indonesian tax authorities should monitor firms with fluctuating leverage ratios more closely, while corporate managers need to align debt policies with tax risk mitigation strategies. This research contributes to the literature by providing empirical evidence from Indonesia.